Voldsulykker i Århus gennem 1 år - Jørgen Nielsen; Sven-Erik Trækjær Jensen; Jess Hedeboe; Bjarne Møller-Madsen; Bjarne Nue Møller; Annie Vesterby; Franz Grymer; Jørgen B. Dalgaard; Jørgen Sommer; Erik Christensen (Nordisk Tidsskrift for Kriminalvidenskab)
See abstract in article.